2011
DOI: 10.1016/j.jcrs.2010.12.055
|View full text |Cite
|
Sign up to set email alerts
|

Determining the local origin of hydroxyl radical generation during phacoemulsification

Abstract: No author has a financial or proprietary interest in any material or method mentioned. Additional disclosures are found in the footnotes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
0
1
0
1
Order By: Relevance
“…Hydroxyl radical concentrations in the aspirated irrigation solution using the torsional modality were approximately one-half that reported for the handpiece's longitudinal modality. 20,21 In their study using ultra-high-speed videos of a phacoemulsifying tip while operating in longitudinal and torsional US modes, Zacharias and Ohl found that cavitation generated by a torsional probe was more fragile than that generated by longitudinal US, which correlates with lower free radical production. 22 In their study, the longitudinal mode was associated with steady cavitation above a threshold value of 60% US power, whereas the torsional mode produced steady cavitation with US power above a threshold value of 80%.…”
Section: Discussionmentioning
confidence: 99%
“…Hydroxyl radical concentrations in the aspirated irrigation solution using the torsional modality were approximately one-half that reported for the handpiece's longitudinal modality. 20,21 In their study using ultra-high-speed videos of a phacoemulsifying tip while operating in longitudinal and torsional US modes, Zacharias and Ohl found that cavitation generated by a torsional probe was more fragile than that generated by longitudinal US, which correlates with lower free radical production. 22 In their study, the longitudinal mode was associated with steady cavitation above a threshold value of 60% US power, whereas the torsional mode produced steady cavitation with US power above a threshold value of 80%.…”
Section: Discussionmentioning
confidence: 99%
“…Mit der Verwendung der Leistungseinstellung von 100% in Gruppe D erhöhte sich der Zellverlust um den Faktor 3-5 gegenüber den Gruppen A, B und E mit der Leistungseinstellung von 50 %. Da in verschiedenen Studien ein nicht linearer Zusammenhang zwischen der Leistungseinstellung und der Kavitationsaktivität festgestellt wurde [21,22], spricht eine solche nicht lineare Abhängigkeit von der Leistungseinstellung für Kavitation als eine entscheidende Schädigungsursache. Andere Autoren haben jedoch einen linearen Zusammenhang zwischen der Leistungseinstellung und Kavitationsanzeigern beobachtet [23,24].…”
unclassified